Concurrent heterozygous Von-Hippel–Lindau and transmembrane-protein-127 gene mutation causing an erythropoietin-secreting pheochromocytoma in a normotensive patient with severe erythrocytosis. Issue 2 (February 2020) - Negro, Aurelio; Graiani, Gallia; Nicoli, Davide; Farnetti, Enrico; Casali, Bruno; Verzicco, Ignazio; Tedeschi, Stefano; Ghirarduzzi, Angelo; Cannone, Valentina; Marco, Loredana D.E.; Filice, Angela; Gemelli, Giuseppe; et al.
Abstract : Background: Mutations of genes related to Krebs cycle enzymes, kinases or to pseudohypoxic signaling pathways, including Von-Hippel–Lindau (VHL) and transmembrane-protein-127 predispose to pheochromocytoma and paraganglioma development. Homozygous loss of function mutation of VHL ( VHL 598C>T ) gene can associate with polycythemia because of an altered hypoxia sensing. Patient: A 19-year-old normotensive man presented with headache, fatigue associated with severe erythrocytosis (hematocrit 76%), high hemoglobin (25.3 g/dl) in normoxic condition. Bone marrow biopsy showed marked hyperplasia of erythroid series. The Janus kinase 2 (V617F) mutation was absent. Abdominal computed tomography scan showed a 8-mm left adrenal pheochromocytoma with tracer uptake on 68 GaDOTA-octreotate PET. Twenty-four-hour urinary metanephrine excretion was slightly increased, while normetanephrine, 3-methoxytyramine were normal. Adrenal veins sampling showed high left-side erythropoietin secretion. Results: Next-generation sequencing genetic analysis evidenced two concurrent heterozygous mutation of VHL598C>T and of transmembrane-protein-127 c.268G>A . Left side adrenalectomy improved symptoms, erythrocytosis, hemoglobin, and erythropoietin circulating levels. Adrenal histologic sections showed a pheochromocytoma with extensive immunostaining for erythropoietin, but also coexpression of chromogranin A, a marker of chromaffin tissue. Conclusion: Congenital polycythemia was clinically diagnosed, mimicking Chuvash polycythemia. Chuvash polycythemia is an autosomal recessive disorder that usually harbors a homozygous mutation of VHL598C>T but not predispose to pheochromocytoma development; in contrast our patient showed for the first time that the concurrent heterozygous VHL and TMEM mutations, resulted in a clinical phenotype of a normotensive patient with polycythemia due to erythropoietin-secreting pheochromocytoma that improved after adrenalectomy.